2020
DOI: 10.1186/s12931-020-01434-9
|View full text |Cite
|
Sign up to set email alerts
|

The IL-17 receptor IL-17RE mediates polyIC-induced exacerbation of experimental allergic asthma

Abstract: Background: The interleukin 17 receptor E (IL-17RE) is specific for the epithelial cytokine interleukin-17C (IL-17C). Asthma exacerbations are frequently caused by viral infections. Polyinosinic:polycytidylic acid (pIC) mimics viral infections through binding to pattern recognition receptors (e.g. TLR-3). We and others have shown that pIC induces the expression of IL-17C in airway epithelial cells. Using different mouse models, we aimed to investigate the function of IL-17RE in the development of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The pro-inflammatory cytokine IL-17C belongs to the IL-17 cytokine family and it is primary expressed by epithelial cells [3][4][5][6][7]. IL-17C shares the IL-17 receptor IL-17RA with IL-17A and regulates inflammation in an autocrine manner through the induction of cytokines, chemokines, and antimicrobial peptides [3][4][5][8][9][10]. The expression of IL-17C in airway epithelial cells is induced by microbial factors and inflammatory cytokines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The pro-inflammatory cytokine IL-17C belongs to the IL-17 cytokine family and it is primary expressed by epithelial cells [3][4][5][6][7]. IL-17C shares the IL-17 receptor IL-17RA with IL-17A and regulates inflammation in an autocrine manner through the induction of cytokines, chemokines, and antimicrobial peptides [3][4][5][8][9][10]. The expression of IL-17C in airway epithelial cells is induced by microbial factors and inflammatory cytokines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Studies of IL-17C in the asthma context are scarce, although recently it was found that knockout of the IL-17RE in mice led to milder virus-induced asthma exacerbations. 21 Whether IL-17C is associated with lung function, airway hyperresponsiveness, asthma control or exacerbation rate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor for IL‐17C, IL‐17RE, is expressed by Th17 cells and IL‐17C activates Th17 cells to increase IL‐17A production and has been shown to recruit neutrophils to the lung 19,20 . Studies of IL‐17C in the asthma context are scarce, although recently it was found that knockout of the IL‐17RE in mice led to milder virus‐induced asthma exacerbations 21 . Whether IL‐17C is associated with lung function, airway hyperresponsiveness, asthma control or exacerbation rate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Combined neutralization of both IL-13 and IL-17A diminished the pathological signs of Th2/Th17 high experimental asthma in mice [ 74 ]. Furthermore, local application of polyinosinic:polycytidylic acid (polyIC) to mice with OVA-induced experimental allergic asthma led to infiltration of IL-17A, producing natural killer (NK) cells and expression of IL-17C, which mediate exacerbation of airway inflammation, mucus hyperproduction, and AHR [ 75 , 76 ]. Since lipopolysaccharide (LPS)-induced exacerbation of experimental asthma in mice is also associated with increased release of IL-17A and can be blocked by an antibody directed against this cytokine, IL-17A could indeed play a significant role during acute asthma exacerbations triggered by bacteria as well as respiratory viruses [ 77 ].…”
Section: Asthmamentioning
confidence: 99%